Cinderella II: Dreams Come True - Kafka, John.; Burton, Corey, 1955-; Holland Taylor; Rob Paulsen; Tress MacNeille (USA Walt Disney Pictures, 2002)
The movie explores Cinderella's ""happily ever after"" life as a princess in 3 stories, with help from the Fairy Godmother. First, Cinderella's awkward first days at the palace, when she tried so hard to fit in that she forgot to be herself. Second, how Jaq felt so left out that he wished to be a human. Third, how Cinderella taught one of her nasty step-sisters how to smile which leads to her own true love.
Jacques and Gus tell the story of how Cinderella becomes a princess but loses touch with herself.
Jill E. Blotevogel
Language(s): English, Greek Subtitle(s): English, Greek
Keywords: Family; Fantasy; Animation